Respuesta :

We have been given the expression

[tex]x^{\frac{9}{7}}[/tex]

We have the exponent rule

[tex]x^{\frac{a}{b}}= x^{a^{(\frac{1}{b})}}[/tex]

Using this rule, we have

[tex]x^{\frac{9}{7}}= x^{9^{(\frac{1}{7})}}[/tex]

Now, using the fact that [tex]x^{\frac{1}{n}}=\sqrt[n]{x}[/tex], we get

[tex]x^{\frac{9}{7}}= \sqrt[7]{x^9}\\ \\ x^{\frac{9}{7}}=\sqrt[7]{x^7\times x^2}\\ \\ x^{\frac{9}{7}}=x\sqrt[7]{x^2}[/tex]

D is the correct option.

Answer

D.  x (⁷√x²)


Explanation

x⁹/⁷  = ⁷√(x⁹)

      = ⁷√(x⁷ × x²)

       = (⁷√x⁷) × (⁷√x²)

        = x (⁷√x²)

The answer is D.

ACCESS MORE